Pelatihan Strategi Online Marketing di Charu Dhatri sebagai Solusi Pemasaran di Era Pandemi - Halwa Annisa Khoiri; Wildanul Isnaini Isnaini; Erdita Nuryanti (Politeknik Negeri Cilacap, 2022)
The community service program targets MSMEs, namely Charu Dhatri. Charu Dhatri is an MSME that produces bags and handicrafts made from jute fabric. These MSMEs have problems regarding marketing and sales during the Covid-19 pandemic. To assist partners in providing alternative sales, online training is held via Zoom. Charu Dhatri already has several social media, but their use has not been maximized due to limited information obtained by partners. In the implementation of this training, Charu Dhatri gained new knowledge about online marketing, optimizing social media by using available digital advertisements and using Etsy media for the promotion and sale of handcraft products abroad. The results obtained from this training there is an increase in knowledge about online marketing by 23.5%. It is hoped that after this training, Charu Dhatri can increase the use of social media so that it has a positive impact on sales. The training was closed by filling out a questionnaire, and the results showed that on average the partners were satisfied with the training provided.